Synthesis of green-emitting carbon quantum dots with excitation wavelength dependent photoluminescence obtained from aqueous beetroot extract. Issue 19 (14th March 2016) - Andrade, George R. S.; Costa, Silvânio S. L.; Nascimento, Cristiane C.; Gimenez, Iara F.
ABSTRACT: In this work, 3 simple, fast, labour and energy efficient methodologies were used to prepare carbon quantum dots (C-dots) using a red beetroot ( Beta vulgaris subsp . vulgaris var . vulgaris ) aqueous extract as the carbon source: alkali-assisted (AA), microwave-assisted (MA) and alkali-microwave-assisted (AMA) synthesis. TEM images shows nanoparticles with a nearly spherical morphology and diameters around 7.0 nm. FTIR spectra show characteristic peaks of C-H, C-O, O-H and C=C bonds for all the samples. The emission spectra show an interesting feature of the as-prepared samples: the emission band position can be tunable by changing the excitation wavelength. Comparing the 3 different methodologies in terms of photoluminescence properties, the one based only on the microwave-assisted heating has showed the most improved emission.